AVALIAÇÃO DE SINTOMAS DEPRESSIVOS E DA QUALIDADE DE VIDA EM PACIENTES COM SÍNDROME FIBROMIÁLGICA - Cabral, Mara Regina Manoeiro (2006)
Fibromyalgia is a syndrome of unknown aetiology with diffuse, widespread and chronicle pain. The diagnosis of the fibromyalgia should be made in agreement with the American College of Rheumatology (ACR) 1990 criteria. The patient should present diffuse pain for more than three months and feel the touch of the physician in at least 11 of 18 sensitive points, called "tending points" that characterizes the syndrome. Most of the patients with it are women, and the pick of age incidence in the occasion of the diagnosis is between 40 and 50 years. The chronic pain promotes a quality impact in the people s life; reducing his/her self-esteem, isolating them of the social relationship and allowing them loose the control of their thoughts and feelings. Depressive symptoms can be the result of the organic dysfunction, associa- ted with the limited conditions of daily activities. The objective of this study is to investigate the presence of depressive symptoms and to analyze the impact of the same ones about on the quality of the patients life with SF. Thirty women, in service from October to November of 2005, were selected with diagnosis of SF and answe- red two questionnaires: Inventory of Depression of Beck, to investigate the presence of depressive symptoms and SF-36 - Medical Outcome Survey Short Form -36, to evaluate the life quality.The statistical results obtained by the program SPS show that the depressive symptoms are responsible for the quality impact in these people's life, mainly in the following aspects: physical, social, mental health, vitality and general health. The analysis of the data suggests that the depressive symptoms can influence in the women life quality with fibromyalgia negatively, because it increases the sensation of physical incapacity, reduces the quality of the social relationships and increases the pessimism, the fatigue and the discouragement